2013
DOI: 10.1111/cas.12278
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidinase‐like protein 3 expression is negatively regulated by MYCN and associated with clinical outcome in neuroblastoma

Abstract: Summary Dihydropyrimidinase-like proteins (DPYSLs) are a family of proteins developmentally regulated during maturation of the nervous system. Recently, members of DPYSL family have been reported to be involved in cancer with low expression of DPYSL1 correlating with poor clinical outcomes in non-small cell lung cancer and functioning as a metastasis suppressor. Neuroblastoma (NB) is a tumor derived from precursor cells of the sympathetic nervous system and is the most common solid tumor in childhood. So far t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Dihydropyrimidinase-like proteins (DPYSLs) are a family of proteins developmentally regulated during maturation of the nervous system. It has been previously established that DPYSLs are negatively regulated by N-Myc and reduced expression levels correlate with poor clinical outcomes [ 36 ]. In accordance with this observation, DPYSL1, 2, 4 and 5 were less abundant in SK-N-BE2 secretome.…”
Section: Resultsmentioning
confidence: 99%
“…Dihydropyrimidinase-like proteins (DPYSLs) are a family of proteins developmentally regulated during maturation of the nervous system. It has been previously established that DPYSLs are negatively regulated by N-Myc and reduced expression levels correlate with poor clinical outcomes [ 36 ]. In accordance with this observation, DPYSL1, 2, 4 and 5 were less abundant in SK-N-BE2 secretome.…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting roles of DPYSL3 have been described in different types of cancer, implying that it has a diversity of functions in different malignancies. Previous studies indicated that DPYSL3 inhibits cell migration by regulating the actin cytoskeleton in neuroblastoma cells [29]. DPYSL3 is also reported to play a role in cell migration and metastasis suppression in liver and prostate cancer [31][32][33].…”
Section: Discussionmentioning
confidence: 97%
“…DPYSL3, also referred to as the collapsing response mediator protein 4, is a member of the DPYSL gene family that is highly expressed in both normal tissues and tumors derived from the lung, colon and prostate [29]. The functions of DPYSL3 involves in various cellular processes, including cell differentiation, migration, neurogenesis and neurodegeneration [30].…”
Section: Discussionmentioning
confidence: 99%
“…S3; Supplementary Tables S12 and S13). Notably, protein expression of dihydropyrimidinase-like 3 (DPYSL3) was high in the fast-growing group 1; this has previously been implicated in neuroblastoma progression (25). Additional proteins with higher levels in group 1 included: Ras GTPase-activating protein-binding protein 2 (G3BP2), involved in Ras signal transduction; stathmin (STMN1), involved in neuroblastoma metastasis (26); cofilin-1 (CFL1) implicated in neuroblastoma susceptibility (27), and microtubule-associated protein (MAP2; ref.…”
Section: Proteomic and Phosphoproteomic Analysis Reveal Molecular Spamentioning
confidence: 99%